Leader Investigation Strategies In The Development Of Marketing Environments To Forther Competitiveness In PT. Prudential Financial Binjai - Lintangdwiyana, Lintangdwiyana; Ramadhani, Sri; Bi Rahmani, Nur Ahmadi (Universitas Ibn Khladun Bogor, 2023)
Strategy is a unified, comprehensive and integrated plan that links the advantages of corporate strategy with environmental challenges and that is designed to ensure that the company's main objectives can be achieved through proper execution by the company. The purpose of this study is to examine more deeply the leadership strategy of leaders in developing marketers to increase competitive advantage at PT. Prudential Sharia Binjai. And to find out the success rate of a leader or leader in developing marketers. The method used is a qualitative descriptive method. Research is written using descriptive where research related to questions through interviews with leaders in a company to obtain results by observing and managing data. The results of this study show the success or success of a leader or leader seen from several factors, namely, agents have increased income, achievement of contests, achievement of travel trips and achievement of MDRT. The strategy used by leaders to develop marketers to increase competitive advantage in the company is to use a communication strategy, where communication is a very important role in increasing competitiveness.